Combating illegal trade in precious metals and gemstones: international strategies and regulatory frameworks (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
The illegal trade in precious metals and gemstones represents one of the most significant challenges to global financial stability and conflict prevention. This trade not only facilitates money laundering and terrorist financing but also perpetuates armed conflicts and human rights violations in resource-rich regions. This article examines the international regulatory frameworks, institutional mechanisms, and collaborative strategies employed to combat illicit trade in precious metals and gemstones, OECD Due Diligence Guidelines, and anti-money laundering measures.The precious metals and stones (PMS) sector encompasses high-value commodities including gold, silver, platinum, diamonds, rubies, emeralds, and other gemstones. While these materials drive legitimate economic activity worldwide, their unique characteristics—high value-to-volume ratio, portability, liquidity, and subjective valuation—make them attractive vehicles for illegal activities.Criminal organizations exploit dealers in precious metals and stones (DPMS) to disguise the origins of illicit wealth, move money across borders undetected, and evade financial scrutiny. The anonymity of cash transactions, ease of resale, and varying levels of regulatory oversight across jurisdictions further enable these illegal activities. Understanding the scope and methods of illicit trade is essential for developing effective countermeasures.